Dental caries status and related factors in children with Attention Deficit and Hyperactivity Disorder (Annals of Medical Research, 2021)
Aim: It was aimed to investigate the caries status and etiological factors of children with Attention Deficit and Hyperactivity Disorder (ADHD), who are reported to have high consumption of cariogenic food and insufficient oral hygiene habits.Materials and Methods: 7-12 year-old children who are newly diagnosed with ADHD and beginning medication (Group 1), who are under medication for a long time (≥6 months) for ADHD (Group 2) and the control group (Group 3) without any diagnosis or drug use are included in the study. The questions about tooth-brushing habits, consumption frequency of sugar added fruit juice, carbonated beverage, fresh fruit, acidic food (chips, biscuits, etc.) were asked. Dental caries prevalence, presence of dental plaque and gingival health status were measured by DFT/dft (decayed-filled tooth number), DFS/dfs (decayed-filled tooth surface number), OHI (oral hygiene index) and MGI (modified gingival index), respectively. The differences between the groups were statistically analysed with the Kruskal-Wallis, and Man Whitney U Test.Results: It was determined that the majority of children in all groups had irregular toothbrushing habits. Daily or every other day consumption of cariogenic foods and beverages were found to be higher in the Group 1 and 2, the highest DFT/dft values were in Group 2 and the highest DFS/dfs values in Group 1, but the differences were not statistically significant (p> 0.05). OHI values in Group 2 were found to be statistical significantly higher than in Group 3 (p=0.000). MGI values were found to be significantly higher in Group 2 than in Group 1 (p=0.011) and Group 3 (p=0.001).Conclusion: Children with ADHD have similar brushing and nutritional habits with healthy children, but they are appear to be at significantly higher risk for oral hygiene and gum disease. They have also higher caries prevalence, although the differences were not statistically significant.
Keywords: Attention deficit and hyperactivity disorder; ADHD; dental caries prevalence; eating habits; oral hygiene habits